A study on suitable habitat for swiftlet farming - Teo,, Wee Chai (Universiti Malaysia Sarawak (UNIMAS), 2009)
Swiftlet farming is a new industry in Sarawak as compared to other longstanding industries such as rubber, palm oil and timber. It is one of the businesses that involved a small capital investment and it can generate enormous returns in future. Swiftlet farming involves the conversion of human-centric building into structures for swiftlet. The purpose of this conversion is to let Swiftlet for nesting and protect them. The design and construction of such building will also helps to accommodate swiftlets’ population. Therefore, in order to increase the productivity of bird nest, study of the suitable habitat for swiftlet should be done thoroughly. Environment factors such as temperature, humidity, ventilation and light intensity are the keys for a successful swiftlet farm house. Internal temperature of building should maintain from 26⁰C to 35⁰C, humidity from 80% to 90%, low air velocity and light intensity less than 5 LUX. Proper ventilation and installation of humidifier could help the building to achieve the desirable range of environment factors. Location of structure will also be considered from direct sunlight direction to reduce the internal temperature. Only licensed swiftlet farming is legal.